Impact of antiandrogen withdrawal syndrome in castration‐resistant prostate cancer patients treated with abiraterone or enzalutamide. (15th September 2020) - Shiota, Masaki; Machidori, Asako; Abe, Tatsuro; Monji, Keisuke; Kashiwagi, Eiji; Takeuchi, Ario; Takahashi, Ryosuke; Inokuchi, Junichi; Yokomizo, Akira; Naito, Seiji; Eto, Masatoshi
Abstract : Objectives: To assess the impact of antiandrogen withdrawal syndrome after bicalutamide withdrawal in castration‐resistant prostate cancer patients treated with androgen receptor‐axis targeted agents. Methods: The study cohort comprised 94 patients treated with abiraterone ( n  = 34) or enzalutamide ( n  = 60) as a first‐line androgen receptor‐axis targeted agent for castration‐resistant prostate cancer despite combined androgen blockade by castration with bicalutamide as the first‐line therapy. The association between clinicopathological factors (including antiandrogen withdrawal syndrome) and therapeutic outcome after using abiraterone and enzalutamide was investigated. Results: The decline in the prostate‐specific antigen level after use of abiraterone or enzalutamide was comparable between patients with and without antiandrogen withdrawal syndrome. Antiandrogen withdrawal syndrome (hazard ratio 3.84, 95% confidence interval 1.29–11.45; P  = 0.016) was associated with a higher risk of progression on multivariate analysis, but not all‐cause death after abiraterone use. Progression‐free survival and overall survival after enzalutamide use did not differ between patients with and without antiandrogen withdrawal syndrome. Conclusions: The present data suggest a modest therapeutic efficacy of abiraterone in castration‐resistant prostate cancer patients with anti‐androgen withdrawal syndrome after bicalutamide withdrawal.